HUBUNGAN MOTIVASI IBU POST PARTUM DENGAN PEMBERIAN KOLOSTRUM PADA BAYI BARU LAHIR DI RSI SITI RAHMAH PADANG TAHUN 2017 - Yussie Ater Merry; Mardiani Bebasari (Ensiklopedia of Journal, 2020)
Based on the initial survey through interviews with post partum mothers at RSI Siti Rahmah Padang, 7 mothers did not give colostrum on the first day of birth. The purpose of this research is to know the relationship of Motivation of Mother Post Partum with the Success of Giving Colostrum to Newborn Baby at RSI Siti Rahmah year 2017. This research type is Analytical Survey with Cross Sectional research design. This study was conducted on 16 to 28 June 2017. The population is all mothers of all Post Partum mothers in the maternity ward RSI Siti Rahmah Padang. Sampling technique taken by Accidental Sampling counted 33 people. Univariate analysis was done manually in the form of frequency distribution table, bivariate analysis was done to see the relation between two variables namely dependent variable and independent variable by using Chi-square statistic. The result of the research showed that from 33 respondents of post partum mother, 57,6% of mothers did not give colostrum to their babies, 63,6% mothers with low motivation, and 54,5% less good role of health officer. There is a correlation between post-partum mother motivation and giving colostrum (p-value = 0,001) days at RSI Siti Rahmah year 2017. It can be concluded that most mothers do not provide colostrum in infants aged 0-3 days, mothers have low motivation, and poor role of health care workers. Therefore, the researcher suggested that mothers increase knowledge to improve the good motivation and counseling delivered by health personnel that the importance of colostrum.